2024
DOI: 10.1002/jnr.25317
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation in obsessive–compulsive disorder: A literature review and hypothesis‐based potential of transcranial photobiomodulation

David Richer Araujo Coelho,
Joshua D. Salvi,
Willians Fernando Vieira
et al.

Abstract: Obsessive–compulsive disorder (OCD) is a disabling neuropsychiatric disorder that affects about 2%–3% of the global population. Despite the availability of several treatments, many patients with OCD do not respond adequately, highlighting the need for new therapeutic approaches. Recent studies have associated various inflammatory processes with the pathogenesis of OCD, including alterations in peripheral immune cells, alterations in cytokine levels, and neuroinflammation. These findings suggest that inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 234 publications
(462 reference statements)
0
0
0
Order By: Relevance
“…It started improving following the first infusion: depression: 15 (moderate), anxiety: 3 (normal), and stress: 4 (normal) two hours after ketamine administration. After a transient deterioration (the stressful academic news regarding academic examination), further improvement was observed with a subsequent second and third infusion to a minimum level (3)(4)(5). This minimum DASS-21 score was sustained during discharge and follow-up at the sixth and 12 th weeks (Table 4).…”
Section: Infusion Proceduresmentioning
confidence: 93%
See 1 more Smart Citation
“…It started improving following the first infusion: depression: 15 (moderate), anxiety: 3 (normal), and stress: 4 (normal) two hours after ketamine administration. After a transient deterioration (the stressful academic news regarding academic examination), further improvement was observed with a subsequent second and third infusion to a minimum level (3)(4)(5). This minimum DASS-21 score was sustained during discharge and follow-up at the sixth and 12 th weeks (Table 4).…”
Section: Infusion Proceduresmentioning
confidence: 93%
“…World Health Organization (WHO) reported that OCD is one of the top 10 most incapacitating illnesses [2]. Around 1.9-3.3% of the global population suffers from OCD [3][4][5][6]. One of the considerable complications of OCD is major depressive disorder (MDD) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%